Achieving commercial-level mass loading in ternary-doped holey graphene hydrogel electrodes for ultrahigh energy density supercapacitors. (April 2018) - Pan, Zhenghui; Zhi, Huozhen; Qiu, Yongcai; Yang, Jie; Xing, Lidan; Zhang, Qichong; Ding, Xiaoyu; Wang, Xianshu; Xu, Guoguang; Yuan, Hua; Chen, Min; Li, Wanfei; et al.
Abstract: Enabling fast ion diffusion in thick electrodes (100–200 µm, 10 mg cm −2 ) is critical for their practical application in state-of-the-art supercapacitors (SCs). We developed a three-dimensional (3D) boron, nitrogen, and phosphorus ternary-doped holey graphene hydrogel (BNP-HGH) film to achieve an optimized porous structure with a high electrical conductivity, large ion accessible surface area, efficient electron and ion transport pathways, as well as high ion adsorption capacity. The binder-free BNP-HGH electrode can deliver a specific capacitance of 350 F g −1 and a volumetric capacity of 234 F cm −3, which are the best performance reported so far for graphene-based SCs using an organic electrolyte. Fully packaged SCs using the BNP-HGH electrodes with a commercial level graphene mass loading (150 µm, 10 mg cm −2 ) can deliver ultrahigh stack gravimetric and volumetric energy densities of 38.5 Wh kg −1 and 57.4 Wh L −1, respectively, which are comparable to those of lead-acid batteries (35–40 Wh kg −1 and 50–90 Wh L −1 ) while maintaining an ultrahigh power density of 83 kW kg −1 ( 55 kW L −1 ) as well as a long cycle life (81.3% capacitance retention over 50, 000 cycles). The high energy and power densities bridge the gap between traditional SCs and batteries, and should be very useful in practical applications. Graphical abstract: fx1 Highlights: A three-dimensional ternary doped holey graphene hydrogel (BNP-HGH) film is developed. The BNP-HGH film electrode delivers a superior capacitance of 350 F g −1 (234 F cm −3 ). It exhibits ultrahigh energy density even with a high mass loading of 10 mg cm - 2 . The assembled device shows an impressive stack energy density of 57.4 Wh L −1 .